The stone giant - Hoglund, Anna. (Wellington, New Zealand, : Gecko Press, 2020)
When her father leaves to save people from a giant who turns them to stone with his gaze, a child in a red dress is left alone. Many days and many nights go by. Every evening the girl says good night to herself in her mirror. When the last light burns down, the girl takes her mirror and a knife and sets out to find her father. "I will save my father from the giant," she says. The Stone Giant is a contemporary and timeless fairytale that tells of a child who succeeds where adults cannot. Based on a classic Swedish fairytale by Elsa Beskow, often called the Beatrix Potter of Scandinavia, whose books have been read by Swedish children for over 100 years.